Number theory Séminaire de théorie des nombres de Paris, 1993-4 - David, Sinnou (London Mathematical Society lecture note series, 1996)
The contributions in this book are based on the lectures delivered at the Seminaire de theorie des nombres de Paris during the academic year 93-94. It is the fifteenth annual volume. This book covers the whole spectrum of number theory, and is composed of contributions from some of the best specialists worldwide. Together they constitute the latest developments in number theory that will be an invaluable resource for all workers in that area.